Leveraging ontochains for distributed public transit ticketing: An investigation with the system for ticketing ubiquity with blockchains - Joseph D. Preece; Christopher R. Morris; John M. Easton (IET Blockchain)
Abstract Transport ticketing systems are crucial for enabling seamless, efficient, and sustainable mobility. However, traditional ticketing systems face limitations such as ticket fraud, lack of interoperability, and the inability to adapt to changes in the dynamic transport networks they issue tickets for. This paper presents new approaches to the system for ticketing ubiquity with blockchains (STUB), a novel smart transport ticketing solution that employs ontochains, a hybrid data structure combining blockchains and ontologies to form a type of distributed knowledge graph. STUB aims to address these limitations by providing a secure, transparent, and flexible platform for ticket issuance, validation, and management. We describe the key components and workflow of the STUB system, highlighting the use of transport network ontologies for modelling complex relationships within transportation systems and blockchain technologies for transport network ontology's state. Additionally, the implementation of Merkle proofs for efficient and secure validation between on‐chain and off‐chain ontological data is discussed. Finally, a simulated toy example is used as a lightweight proof‐of‐concept to demonstrate these capabilities. The proposed STUB system has the potential to significantly impact the future of transportation ticketing by offering a more seamless, interoperable, and user‐friendly experience whilst addressing the challenges associated with traditional ticketing systems.